Effect of Organizational Culture and Empowerment on Organizational Commitment to Improve Employee Performance - Wulandari, Astrilia (Bina Bangsa International Journal of Business and Management, 2023)
This study aims to examine the effect of Organizational Culture and Empowerment on Organizational Commitment to improve Employee Performance at Puskesmas Ngemplak 1. This research was conducted on all employees of Puskesmas Ngemplak 1, totaling 40 people. This research is quantitative in nature. The sample of this study used a sampling technique with a questionnaire or questionnaire. The sample data collection was carried out by distributing questionnaires directly to each employee. The number of questionnaires distributed and processed was as many as 20 questionnaires. Data processing in this study uses multiple linear regression analysis techniques, assisted by the SPSS program version 20.0. The results of this study indicate that organizational culture has a positive and significant effect on organizational commitment. Organizational culture has a positive and significant effect on performance. Empowerment of members has a positive and significant effect on organizational commitment. Empowerment of members has a positive and significant effect on performance and organizational commitment also has a positive and significant effect on performance. This proves that organizational culture and member empowerment on organizational commitment greatly affect the performance of the employees of Puskesmas Ngemplak 1